Dakwah dan Fenomena Islam Liberal - Iskandar (Fakultas Ushuluddin, Adab, dan Dakwah IAIN Parepare, 2020)
Muslims are now in the modern era which is marked by the emergence of very complex contemporary problems. Liberal Islam sees this phenomenon as one of the renewal movements. The liberal group wants complete freedom and demands individual rights as freely as possible to express themselves in accordance with the times. This includes freedom in rituals and religious contexts, as well as Islamic teachings. So that the Islamic reform movement emerged so that it could be adapted to the rational conditions of the times and in accordance with the issues of modernity. The aims of this study include analyzing the concept of Islamic da'wah and the thoughts of the liberalism movement in Islam. This article uses a descriptive qualitative method. The results of this study found the ideal concept of da'wah, namely a building that has a foundation on the words of Allah in the Qur'an by elaborating through the sunnah of the Prophet Muhammad SAW. Then the next da'wah concept that needs to be developed is to build the same perception among the Muslim community, both da'i and mad'u, that Islam is one, but its expressions vary. Some show expressions that are traditional, modernist, liberal and so on. While liberalism is an understanding that seeks to enlarge the area of individual freedom and encourage social progress. Liberalism is a system of thought whose foundation is a free human being. Free, because humans are able to think and act according to what they want. And this means that liberalism is an understanding of optimistic thinking about humans.